2009
DOI: 10.2215/cjn.01840309
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia Associated with Tunneled Hemodialysis Catheters

Abstract: Background and objectives: Treatment without catheter replacement (catheter salvage) has been described for bacteremia associated with tunneled venous catheters in hemodialysis patients, but few data are available on which to base an estimation of the likelihood of treatment success.Design, setting, participants, & measurements: In a prospective cohort study, all cases of catheter-associated bacteremia that occurred in a large dialysis center were identified during a 12-mo period. Catheter salvage was attempte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 22 publications
5
39
0
Order By: Relevance
“…Six articles also noted results of patients that had catheter removal/replacement. These patients' clinical pictures were similar to the patients' clinical pictures who underwent guidewire exchange in one study, 32 but in other studies, it was clearly reserved for those patients with sepsis or severe disease 10,16,31 or was unclear. 3,15 Individual study characteristics are described in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 53%
See 1 more Smart Citation
“…Six articles also noted results of patients that had catheter removal/replacement. These patients' clinical pictures were similar to the patients' clinical pictures who underwent guidewire exchange in one study, 32 but in other studies, it was clearly reserved for those patients with sepsis or severe disease 10,16,31 or was unclear. 3,15 Individual study characteristics are described in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 53%
“…Several studies report success rates between 66% and 89% when CRB was treated with removal and subsequent replacement of the HD catheter. 3,15,16,32 The two strategies (guidewire exchange and removal/replacement) do not show a difference in outcome in two studies, 3,32 whereas removal/replacement showed a higher success rate in one study, 15 although they are all nonrandomized observational studies. The results of this meta-analysis suggest that the use of guidewire exchange for S. aureus or GNR bacteremia may be a reasonable up-front treatment option.…”
Section: J Am Soc Nephrol 25: 2927-2941 2014mentioning
confidence: 96%
“…An alternative option is to leave the catheter in place and to attempt catheter salvage instilling an antibiotic lock (see below, 'Antibiotic locks') in addition to systemic antibiotic therapy [72,73] (30)(60). In a recent study, catheter salvage after incident bacteraemia achieved a cure, defined as no recurrence or complication, in 66.1% of cases [74]. Recurrent bacteraemia was less common after catheter removal and reinsertion than after salvage (8.1 vs 33.0%) but at the expense of dramatically more complications (14.3 vs 0.9%).…”
Section: Management Of Catheter Infection In Patients Receiving Haemomentioning
confidence: 95%
“…The second mechanism is blood exposure to contaminants, which may be present in the dialysate and may cross the dialysis membrane by back-diffusion and back-filtration stimulating monocyte activation [27]. A third component concerns the possible presence of catheters or synthetic grafts with tunnel or exit site infection, which represents a source of infection and inflammation [28,29]. Additionally, fluid overload should also be considered an important cardiovascular risk factor responsible for extracellular volume expansion and ventricular enlargement [30,31].…”
Section: Epidemiology and Pathophysiology Of Crs Typementioning
confidence: 99%